Revealing the Instagram "Grid Zero" Trend Among Gen Z Through Interactive Learning Media Slido - Faqihul Muqoddam; Ni Putu Rizky Arnani; Ahmad Najibullah (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2026)
The high number of Instagram users among Generation Z and the emergence of the “Grid Zero” trend highlight the need for research to understand why they choose to empty their Instagram feeds. This study aims to explain the reasons Gen Z participate in the Grid Zero trend. Data were collected through a survey involving 100 Gen Z participants (n=100) who had no posts on their personal Instagram accounts. The survey was conducted using the interactive platform Slido through Polling, Open Text, and Word Cloud features; the responses were then analyzed thematically. The findings reveal seven main themes underlying Gen Z’s adoption of the Grid Zero trend: lack of self-confidence, feelings of saturation and boredom, maintaining emotional stability, self-transformation, religious practices, aesthetics, and social demands. The results also shed light on Instagram usage duration and the length of time participants engaged in Grid Zero. This study is expected to provide deeper insights into Gen Z’s motivations for following the Grid Zero trend, offering valuable insights for parents, educators, and the community regarding Gen Z's digital behavior.